Dual-band microwave bandpass filters for advanced wireless communication - Meng, Fanzeng. (2013)
Microwave filters are widely used in the modern wireless communication systems. Thus in this project, the aim is to design a Compact Dual-Band Microwave Bandpass Filter for advanced wireless communication. The filter is designed to operate at 1.8GHz and 5.8GHz without external impedance-matching block and simulated using Advanced Design System (ADS) software. The modified quarter-wavelength stepped-impedance resonator is constructed to excite the dual resonances at the two specified frequencies. The external parallel-coupled microstrip line is designed to minimize the return losses within both bands. To achieve the good filtering performances, the return losses for the two bands should be higher than 20 dB.